Means of Temporal Expressions in Newspaper News and Press Report - Čutura, Ilijana R.; Spasić, Jelena Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper analyses most frequent linguistic means for expressing the temporal frame in the printed news and press reports. With structuralism as a chosen theoretical framework, the approach of the research is qualitative and stylistic. Since the study belongs to the field of functional stylistics, the primary methods used in the study were functional-stylistic and linguistic-stylistic ones. As the study focuses on two newspaper genres, comparative-stylistic method was used as well. The analysis has been conducted on concrete linguistic excerpts from Serbian daily newspapers published throughout Serbia from 2008 to 2015. The aims of the paper are to show model of expressing temporal frame in contemporary Serbian newspapers. This paper provides an overview of the characteristics of model and the types of temporal epression as well as their variations in contemporal Serbian newspapers. The paper also aims to determine the differencies between printed news and press reports by the choice of temporal expressions. It is shown that there is a tendency of changing schematised structure of these informative genres and some innovation in relation to the choice of linguistic means for expessing the meaning of temporally close events. The research is a contribution to journalism stylistics, more precisely to the Serbian language newspaper stylistics, and also contributes to the study of linguistic and stylistic characteristics of non-literary texts. The study is also relevant because it describes the use of adverbs and adverbial expressions in the journalistic style.